Влияние некоторых препаратов на жизнедеятельность тутового шелкопряда при «спонтанной» желтухе - Ацеховская, Н.В. (Вестник зоологии, 1969)
An estimation is given of the effect of tartaric acid, glycol, cobalt and lithium chloride salts, potassium thiocyanate, and copper sulphate on viability and resistance of the Bombyx mori hybrid YC-1XBel-2, industrially reared under conditions of a spontaneous nuclear polyhedrosis at a collective farm in the Odessa region. The positive effect (especially that of copper sulphate) on the appearance of imago and on the process of laying eggs was observed in all six experimental variants. An assumption is made that lithium chloride and potassium thiocyanate can also be used for a directional action on histogenesis of animals.